2007
DOI: 10.1016/j.foodchem.2006.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition of the liver oil of the ray, Himantura bleekeri

Abstract: If rays are traditionally fished for their caudal fins, the rest of the body is wasted, except part of the skin that can be transformed into leather. Liver oil of the ray, Himantura bleekeri, was characterized in terms of lipid class composition and fatty acid profile. Liver oil content was high and represented 54% of the liver weight (w/w). Neutral lipids were predominant (92%), major components being triacylglycerols (63%). Other neutral lipids identified were hydrocarbons, sterol esters, mono-and diacylglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…The fatty acid profiles exhibited a dominance of unsaturated fatty acids (UFAs) for all samples exceeding 65% of the total fatty acid content. These findings are in line with those previously reported by Navarro-Garcia et al (2004) and Le Nechet et al (2007). Among the saturated fatty acids (SFAs), those occurring at the highest proportions were palmitic acid (C16:0, ranging from 19.8% to 24.52%) followed by stearic acid (C18:0, ranging from 2.34% to 6.77%) and myristic acid (C14:0, ranging from 0.57% to 1.06%).…”
Section: Oil Characterizationsupporting
confidence: 94%
See 1 more Smart Citation
“…The fatty acid profiles exhibited a dominance of unsaturated fatty acids (UFAs) for all samples exceeding 65% of the total fatty acid content. These findings are in line with those previously reported by Navarro-Garcia et al (2004) and Le Nechet et al (2007). Among the saturated fatty acids (SFAs), those occurring at the highest proportions were palmitic acid (C16:0, ranging from 19.8% to 24.52%) followed by stearic acid (C18:0, ranging from 2.34% to 6.77%) and myristic acid (C14:0, ranging from 0.57% to 1.06%).…”
Section: Oil Characterizationsupporting
confidence: 94%
“…For example, fatty acid distributions in the muscle, liver, and gonads of three ray species (Dasyatis marmorata, Rhinobatos cemiculus, and Rhinoptera marginata) from the east tropical Atlantic Ocean were determined by Ould El Kebir et al (2003). Also, liver lipids of Dasyatis brevis and Gymnura marmorata from the California Gulf (Navarro-Garcia et al, 2004) and Himantura bleekeri from the Indian coast (Le Nechet et al, 2007) were analyzed. These authors had found that the liver lipidic fractions of all ray species studied contained a high amount of PUFAs (up to 30% of the total lipids), mainly composed of DHA and EPA.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the highest amount in our study period was noted for PUFA n-3. A high level of cholesterol is required for the biosynthesis of sex and molting hormones (Kanazawa 2001), as well as for the formation of cell membranes and intercellular structures in crustaceans (Le Nechet et al 2007). Cholesterol is also an intermediate in the biosynthesis of ecdysteroids (Hopkins 2009).…”
mentioning
confidence: 99%
“…Saify ZS et al (2000) found that the lipid content in the liver of Hammer-headed Shark Eusphyra blochii (66.19 %) was higher than that of shark Carcharhinus bleekeri (39.94 %). 47 Similarly, 48 reported that oil extracted from the liver of ray fish Himantura bleekeri confirmed that the liver is relatively rich in lipids which implies 54 % of the fresh matter containing lipids. In accordance with previous studies, lipid content of other elasmo branch livers was ranging from 23 to 67 % 49, [50][51][52][53] reported that the lipid content of liver of Dasyatis brevis and Gymnura marmorata as 50.80 % and 51.50 % of the total lipids respectively.…”
Section: Discussionmentioning
confidence: 92%